2020
DOI: 10.17582/journal.aavs/2020/8.3.278.284
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Escherichia coli Isolated from Döner Kebab Sold in Dramaga Bogor, Indonesia

Abstract: This study was aimed to determine the occurrence of antibiotic resistance in Escherichia coli (E. coli) isolated from Döner kebab sold in Dramaga Bogor, West Java Province, Indonesia. A total of 43 samples of Dὂner kebab meat were taken from all of the vendors in the radius of 2 km around the border of IPB University campus, Dramaga Bogor. Isolation and identification of E. coli were referred to the Guideline for Laboratory Analysis on Examination of Microbial Contamination in Meat, Egg, and Milk in SNI 2897:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Konsumsi susu yang mengandung residu antibiotik dapat menimbulkan gejala diare, keracunan maupun gejala alergi (Detha, 2014). Mikroba dapat masuk kedalam susu segar secara langsung dari sapi perah, dari lingkungan peternakan, sumber air dan peralatan yang digunakan untuk penyimpanan susu di peternakan atau selama transportasi (Ravi, 2020).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Konsumsi susu yang mengandung residu antibiotik dapat menimbulkan gejala diare, keracunan maupun gejala alergi (Detha, 2014). Mikroba dapat masuk kedalam susu segar secara langsung dari sapi perah, dari lingkungan peternakan, sumber air dan peralatan yang digunakan untuk penyimpanan susu di peternakan atau selama transportasi (Ravi, 2020).…”
Section: Pendahuluanunclassified
“…al. lembaga ini melaporkan bahwa prevalensi antibiotika di wilayah Jawa Barat cukup tinggi, terutama Bogor yaitu 3.06% untuk penisilin, 28.57% untuk makrolida, 2.55% untuk aminoglikosida, dan 47.45% untuk tetrasiklin. Bakteri E. coli resistan terhadap antibiotik penisilin (95.2%), streptomisin (84,3%), kolistin (76.9%), amoksilin (74.2%) dan tetrasiklin (62.5%) (Ravi 2020). Antimikroba yang sering digunakan dalam pengobatan penyakit pada sapi perah menurut Page dan Gautier (2012) adalah penisilin, streptomisin dan sefalosporin.…”
Section: Pendahuluanunclassified
“…Moreover, ESBL-producing E. coli was found in 8.6% of cattle feces from slaughterhouses [ 26 ], and multi-drug resistant (MDR) E. coli was reported in 57.3% of swine fecal samples [ 14 ]. MDR among AMR E. coli was also found in 25% from Döner Kebab meat in Bogor, Indonesia [ 23 ]. These results indicated that a variety of AMR phenotypes in E. coli were existed and might be a widespread in the environment, Indonesia.…”
mentioning
confidence: 99%